GAMBARAN KLINIS DAN LABORATORIUM SINDROM SYOK DENGUE RAWAT PICU RSU DR. SAIFUL ANWAR MALANG - Budhy, Setya; YS, Mardhani; Muid, Masdar (Fakultas Kedokteran Universitas Brawijaya, 2004)
ABSTRACT Dengue shock syndrome (DSS) is a clinical emergency case with still high mortality rate. During five years period (1January 1997?31 December 2001) total case of SSD triaded in PICU room Medical Faculty Brawijaya University/ Saiful Anwar Hospital Malang were thirty two patients. They were referred from Malang regency 9 patients (28%), Malang city 23 patients (72%). The most group age 6 ? 10 years 14 patients (44%), < 5 years 13 patients (41%), 11 ? 14 years 5 patients (15%). SSD is devided in DBD grade III 14 patients (44%), DBD grade IV 18 patients (56%). Laboratory finding total leucocyt count < 4000/mm3 8 patients (25%), 4000 ? 10000/mm3 24 patients (75%). Total thrombocyt < 50000 / mm3 22 patients (69%), 50000 ? 100000/ mm3 10 patients (31%). Hematocrit > 42% all patients (100%). Clinical sign found in SSD patients quickly and fine pulse 14 patients (44%), cold extremities 32 patients (100%), pulse not palpable 18 patients (56%). Blood tension : unmeasured 18 patients (56%), hypotension 18 patients (56%). Death patients 13 (41%) recovery patients 19 (59%). All SSD patients (100%) were death by complication of occult bleeding, pulmonary edema, respiratory failure.